Grow-out of Oreochromis niloticus (Linnaeus, 1758) fish (Perciformes, Cichlidae) on Local Feed in an Above-ground Tank Culture System in Kinshasa, Democratic Republic of Congo - Kiamfu, Victor Pwema; Luila, Josette Mbaki; Kumutima, Berthe Kazaba; Matondo, Alex Mayoni; Nzege, Christian Yaga; Lusasi Swana, Willy (Talenta Publisher, 2023)
Acquiring land that meets the required standards for lowland ponds is becoming an increasing problem in the city of Kinshasa in the Democratic Republic of Congo, and fish farming in above-ground concrete tanks is emerging as an alternative. The objective of this study was to follow the evolution of pre-growth of Oreochromis niloticus Linnaeus, 1758 in an above-ground concrete tank culture system using feed based on local agricultural by-products available in Kinshasa. A total of 198 fries were distributed in 3 tanks and fed three times a day. The experiments were conducted for 60 days between August and November 2021. The results obtained indicate a better survival rate (T1 = 75.75±4.32%; T2 = 60.6±9.76% and T3 = 83.33±4.96%). Feed T1 (mean weight = 33.15±2.78 g) and T2 (28.44±3.76 g) had a positive impact on fish weight growth. The cost of producing one kilogram of a feed ration varied depending on the ingredients used. It cost 2,843 FC to develop the T1 feed, 951 FC to produce the T2 feed and 5.000 FC to afford the T3 commercial feed sold in Kinshasa. Ration T2 is the one that gave a better compromise of price and quality by promoting good fish growth at a lower cost (1,692 Congolese Francs) than the other two feeds. These observations sufficiently show that during the experiment, the experimental structure (concrete tank) did not have negative effects on the zootechnical performance of the fry of the fish species studied. The economic aspect of the use of feed rations by fry showed the merits of rearing fish using local agricultural by-products rather than commercial feed. This study showed the merits of setting up an above-ground concrete tank fish farm to overcome the difficulty of acquiring land to meet fish farming requirements.